USE OF MULTIVARIATE DISCRIMINATE ANALYSIS FOR THE PREDICTION OF RISK OF ARTERIAL HYPERTENSION IN ADOLESCENTS - L. V. Natyaganova (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
69 adolescents of 14-17 years with essential arterial hypertension (EAH) were examined. The most informative indices of lipid peroxidation and antioxidant defense (LPO - AOD) in the blood of adolescents were studied. The state of LPO - AOD system was assessed by determining diene conjugates, ketodienes and conjugated trienes concentrations, superoxide dismutase activity and total antioxidant activity. A method for prediction of the risk of essential hypertension in adolescents was proposed using multivariate discriminant analysis.